History of Science, History of Text
XXVIII, 266 p.
Keywords: This book explores the hypothesis that the types of inscription or text used by a given community of practitioners are designed in the very same process as the one producing concepts and results. The book sets out to show how, in exactly the same way as for the other outcomes of scientific activity, all kinds of factors, cognitive as well as cultural, technological, social or institutional, conjoin in shaping the various types of writings and texts used by the practitioners of the sciences. To make this point, the book opts for a genuinely multicultural approach to the texts produced in the context of practices of knowledge. It is predicated on the conviction that, in order to approach any topic in the history of science from a theoretical point of view, it may be fruitful to consider it from a global perspective. The book hence does not only gather papers dealing with geometrical papyri of antiquity, sixteenth century French books in algebra, seventeenth century scientific manuscripts and paintings, eighteenth and nineteenth century memoirs published by European academies or scientific journals, and Western Opera Omnia. It also considers the problems of interpretation relating to reading Babylonian clay tablets, Sanskrit oral scriptures and Chinese books and illustrations. Thus it enables the reader to explore the diversity of forms which texts have taken in history and the wide range of uses they have inspired. This volume will be of interest to historians, philosophers of science, linguists and anthropologists.